'And suddenly I saw the bowl': utilizing the paradoxes of Whiteness to combat its ephemerality in the White mind. Issue 2 (3rd July 2022) - Boucher, Colleen
ABSTRACT: Whiteness is defined by its normalcy and invisibility in white minds, and while those who have been made conscious of their own whiteness may grasp it in particular instances, the pervasiveness of the privileges and wages of whiteness is elusive for most whites. It would seem that whiteness is ephemeral in the white mind, which may comprehend the existence of whiteness theoretically but then fail to see it lived out. Much like the fishbowl in Morrison's (1992) metaphor of whiteness, the ordered world of privileges is protected by transparent glass that is difficult to perceive from the inside. Using the paradoxes of silence through invisibility, discomfort, and the fact that whites must end whiteness, this paper analyses the ways the paradoxes of whiteness can be utilised to combat its ephemerality in the white mind.